2018
DOI: 10.1111/cid.12644
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of volumetric wear of abutments on the retention loss of ball attachment systems in implant‐retained overdentures: An in vitro study

Abstract: Within the limitations, it can be concluded that although clinical studies are needed to ensure the findings of the present study, due to severe retention loss and volumetric abutment wear, ball attachments with titanium female components should be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 27 publications
4
16
0
4
Order By: Relevance
“…At this site, the retention forces increased slightly but significantly, after 1 year. This short‐term increase was also observed in previous in vitro studies, evaluating ball attachments . It was related to the plastic strain of the matrices, which caused an interference of the coupling components and consequently an increased retention force .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…At this site, the retention forces increased slightly but significantly, after 1 year. This short‐term increase was also observed in previous in vitro studies, evaluating ball attachments . It was related to the plastic strain of the matrices, which caused an interference of the coupling components and consequently an increased retention force .…”
Section: Discussionsupporting
confidence: 77%
“…The decrease that was found in the other studies could be related to changes at the male part, the female part, or both. An in vitro study, analyzing volumetric changes at the male part in IODs showed that male parts lost volume due to wear over time . This can be a critical issue, especially in one‐piece implants, as the male parts cannot be replaced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the dental implants represent successful and prospective treatment modality to the edentulous patients. Actually; implants would improve the denture support, retention and stability that in turn ameliorate patients’ satisfaction (3). Moreover, it has been revealed that; people with dental implants treatment provide almost double biting forces than that with complete denture (4,5).…”
Section: Introductionmentioning
confidence: 99%